Evaluation of Novel Probiotic Bacillus Strains Based on Enzyme Production and Protective Activity Against Salmonellosis - Ghorban Hosseini, Nazila; Modarressi, Mohammad Hossein; Mousavi, Seyed Naser; Tajabadi Ebrahimi, Maryam (Journal of the Hellenic Veterinary Medical Society, 2019)
Probiotic strains of Bacillus Species are used in industrial poultry production because of their ability to produce enzymes enhancing the absorption of food, and their ability to reduce the risk of Salmonella spp. infection. The aim of this study was to isolate native potential probiotic Bacillus spp. with the ability to produce enzymes and attachment to intestinal epithelial cells in order to prevent Salmonella typhimurium infection. First, 25 samples of chicken feces were collected from 7 industrial poultry in Golestan province located in north of Iran. Bacillus species from samples were isolated on nutrient agar. These strains were evaluated for the ability of producing amyalse and phytase and their probiotic characteristics such as bile salt, acid and antibiotic resistance, the ability to attach to intestinal epithelial cells and inhibit Salmonella typhimurium invasion. Then selected isolates were identified based on 16S rDNA. Results showed that from 86 isolated, 4 Bacillus strains‌ had desirable characteristics such as the ability to produce phytase and amylase and having suitable probiotics features. We identified K03, K02, and K20 isolates as Bacillus tequilensis and K20 as Bacillus subtilis. Bacillus tequilensis K03 showed the highest attachment ability to intestinal epithelium cells and could inhibited Salmonella typhimurium attachment.